Anti-myocardial ischemia effect of Syringa pinnatifolia Hemsl. by inhibiting expression of cyclooxygenase-1 and -2 in myocardial tissues of mice. (1st July 2016) - Cao, Yuan; Wang, Jing; Su, Guozhu; Wu, Yan; Bai, Ruifeng; Zhang, Qian; Gao, Xiaoli; Li, Chun; Chen, Suyile; Tu, Pengfei; Chai, Xingyun
Abstract: Ethnopharmacological relevance: The peeled stem of Syringa pinnatifolia Hemsl. (SP) is a traditional medicine in Inner Mongolia, China. The powder form of SP has been widely used for hundreds of years to relieve "He-Yi" related myocardial ischemia independently or in a traditional Chinese medicine preparation. Materials and methods: SP was extracted with 95% and 80% ethanol. Chemical profiling was performed using HPLC-DAD and IT-TOF-ESI-MS analyses. Myocardial ischemia was produced by ligation of the left anterior descending (LAD) coronary artery to evaluate the anti-myocardial ischemia effect of SP. Male C57BL/6 mice were randomly divided into six groups (n=10 per group): a sham group, a model group, groups pretreated with SP at three dosages (20 mg/kg, 40 mg/kg, and 80 mg/kg, intragastrically), and a positive control group (acetylsalicylic acid, ASA, 53 mg/kg, intragastrically). Echocardiography was performed to determine heart function by measuring ejection fraction and fractional shortening. The levels of creatine kinase-MB (CK-MB) and lactate dehydrogenase (LDH) in serum, and 6-keto-PGF1 α and TXB2 both in plasma and in protein homogenate of myocardial tissue were also measured. The levels of cyclooxygenase (COX)-1 and -2 in the heart tissue and their expressions in mouse myocardial tissue were determined using Western blot and an immunofluorescence assay, respectively. Inflammatory cell infiltration and collagen deposition changes in the myocardial ischemic tissue were observed by pathological examination. Results: Intragastric pretreatment with SP produced a dose-dependent increase in cardiac function. SP at 80 mg/kg significantly improved the EF ( p <0.001) and FS ( p <0.01) compared with the model group, as well as the levels of serum CK-MB and LDH decreased obviously ( p <0.001), approaching those in the sham group. Besides, an obvious reduction in inflammatory cells infiltration and collagen deposition in the infarcted myocardial tissue was shown in each SP treatment group. In addition, SP increased 6-keto-PGF1 α and decreased TXB2 levels in the plasma, whereas the opposite pattern was observed in the protein homogenate from the myocardial tissues at the infarction edge, but keeping balance the ratio of 6-keto-PGF1 α and TXB2, which is better than ASA in plasma. The mechanisms is associated with the downregulated expressions of COX-1 ( p <0.05) and COX-2 ( p <0.001). Conclusions: Ethanol extract of SP has a protective effect against myocardial ischemia via down regulation of COX-1 and COX-2 expression and by adjusting the ischemia-induced imbalance between 6-keto-PGF1 α and TXB2 . This study shows substantial evidence to support the clinical application of SP and indicates that such medicine has great potential for treating ischemia-induced heart disease. Graphical abstract: